Antibacterial Activity and Microstructure properties of Copper Oxide particles Doped with Cadmium Prepared by Chemical Precipitation Method - Shatha Batros; farqad rasheed; hussein hussein (Iranian Journal of Materials Science and Engineering)
The copper oxide nanoparticles were synthesized using a precipitation method, recognized for its significance in antibacterial applications. This study reports the synthesis of pure CuO and CuO:Cd nanoparticles at two different concentrations, and explores their structural properties and antibacterial activity. The structural characteristics of the prepared powders were analyzed using X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive spectroscopy (EDS). Raman spectra were also examined using a 543 nm laser wavelength. XRD analysis confirmed that the as-synthesized samples exhibit a face-centered monoclinic structure, with crystallite size decreasing as dopant concentration increases, as estimated using the Scherrer method. The obtained crystallite sizes ranged from 7.13 to 11.72 nm, likely due to the larger atomic radius of Cd compared to Cu. The major Raman lines observed included Au2 (156 cm^-1), Ag (∼294 cm^-1), Bu2 (∼598 cm^-1), and lines at 1100 cm^-1 and 1420 cm^-1. The antibacterial activity of the synthesized CuO and CuO:Cd specimens was evaluated using the Kirby-Bauer disk diffusion method against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli bacteria. The antibacterial activity increased with higher Cd concentrations and smaller particle sizes, resulting in larger inhibition zones and higher percentage inhibition ratios for both types of bacteria. The copper oxide nanoparticles were synthesized using a precipitation method, recognized for its significance in antibacterial applications. This study reports the synthesis of pure CuO and CuO:Cd nanoparticles at two different concentrations, and explores their structural properties and antibacterial activity. The structural characteristics of the prepared powders were analyzed using X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive spectroscopy (EDS). Raman spectra were also examined using a 543 nm laser wavelength. XRD analysis confirmed that the as-synthesized samples exhibit a face-centered monoclinic structure, with crystallite size decreasing as dopant concentration increases, as estimated using the Scherrer method. The obtained crystallite sizes ranged from 7.13 to 11.72 nm, likely due to the larger atomic radius of Cd compared to Cu. The major Raman lines observed included Au2 (156 cm^-1), Ag (∼294 cm^-1), Bu2 (∼598 cm^-1), and lines at 1100 cm^-1 and 1420 cm^-1. The antibacterial activity of the synthesized CuO and CuO:Cd specimens was evaluated using the Kirby-Bauer disk diffusion method against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli bacteria. The antibacterial activity increased with higher Cd concentrations and smaller particle sizes, resulting in larger inhibition zones and higher percentage inhibition ratios for both types of bacteria.